Conservative treatment for Brucella testicular abscesses: A case report and literature review - Tahaineh, Sakher; Abu Mughli, Rawan; Hakami, Hanan I; Al-Faham, Mohamad I (Canadian Urological Association Journal, 2015)
Brucellosis is a multi-organ infectious disease that can cause genitourinary manifestations. The most common genitourinary manifestation is orchitis; however, intratesticular abscesses are a rare complication. Although surgery is the standard treatment for intratesticular abscesses, medical therapy alone can be successful. We report the case of a 36-year-old man with multiple testicular abscesses caused by relapse of systemic brucellosis. The patient presented after a history of treated systemic brucellosis with left testicular swelling and pain. An ultrasound showed multiple small testicular abscesses, and the repeat diluted brucella titer demonstrated the causative pathogen. The patient was successfully treated with 3 months of oral targeted antibiotics, with no need for drainage or orchiectomy.